Pengolahan Limbah Ternak Sapi Secara Sederhana di Desa Pattalassang Kabupaten Sinjai Sulawesi Selatan - Adityawarman, A. C.; Salundik, Salundik; Cyrilla, L. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Waste could be problem if doesn’t handled properly make bad impact on environment. The treatment exacly on livestock waste will provide addition value of livestock waste. The treatment of livestock waste processing to biogas, solid manure, and liquid manure is good metode to minimize the impact of livestock waste pollution. The biogas used to be alternative fuel substitute fuel oil or LPG for cooking. The effluent reus to be solid manure and liquid manure by liquid and solid separation, this metode advantage cause zero waste. The other advantage is give more income for farmer. Data analized by bruto margin analized is the comparisons of benefits and loss which obtained by applied new technology to know worthy or not this technology applied. The result of accounting sawed biogas instalation 1.6 m3 per day give more income Rp 1 300 184 per mount.